2022
DOI: 10.1002/2211-5463.13367
|View full text |Cite
|
Sign up to set email alerts
|

Paired related homeobox 1 attenuates autophagy via acetyl‐CoA carboxylase 1‐regulated fatty acid metabolism in salivary adenoid cystic carcinoma

Abstract: Autophagy can affect the invasion and metastasis of carcinoma. Our previous study has shown that invasion and epithelial‐mesenchymal transition in salivary adenoid cystic carcinoma (SACC) can be promoted by the metabolic reprogramming of free fatty acids (FFAs). However, the effect of FFA metabolism on autophagy in SACC remains unknown. In this study, we showed that overexpression of paired related homeobox 1 (PRRX1) reduced the number of autophagosomes and decreased the expression of LC3 and Beclin‐1 in SACC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Recent studies have demonstrated that autophagy is involved in tumorigenesis, tumor development, and chemoradiotherapy resistance [19,[24][25][26]. Investigations of autophagy in patients with ACC have revealed that autophagy-related genes are involved in ACC tumorigenesis and can serve as prognostic factors [6,7,[27][28][29][30][31]. Moreover, autophagy inhibition can improve ACC chemosensitivity [30].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that autophagy is involved in tumorigenesis, tumor development, and chemoradiotherapy resistance [19,[24][25][26]. Investigations of autophagy in patients with ACC have revealed that autophagy-related genes are involved in ACC tumorigenesis and can serve as prognostic factors [6,7,[27][28][29][30][31]. Moreover, autophagy inhibition can improve ACC chemosensitivity [30].…”
Section: Introductionmentioning
confidence: 99%